Strategic actions of urban development to define the intervention policies of slums - Amany Ragheb; Rasha El-Ashmawy (City, Territory and Architecture, 2021)
Abstract The problem of slums is one of the most imperative problems experienced by many developing countries as well as some developed countries. The random gatherings shape real disruption in the economic and social development plans of the concerned countries. The importance of the research lies in conducting a field study for Ezbet El-Shahatin area in Mansoura city, given that it is the largest unplanned informal area in Dakahlia Governorate in terms of area. Geographic information systems were used to make enter data to form a coordinated database. In addition, policy intervention matrix in slums was used to make the appropriate decision regarding the development of the area. The study concludes to specifying several recommendations to deal with slums and set a model for integrated urban development in low-income areas that can be repeated in other similar locations.